Evaluating School Zoning as a Policy Instrument for Promoting Educational Equity - Milwan, Milwan; Sari, Jayanti Armida (Universitas Teuku Umar, 2025)
This study aims to investigate the factors influencing policy effectiveness and strategies for achieving goals, addressing challenges like inadequate communication, resource gaps, and stakeholder disparities. The data collection method used is a literature study from various recent studies (2019-2023) to access the latest information and data. A SOAR analysis is conducted to formulate strategies for implementing the policy in Indonesia. Key findings highlight the importance of clear communication, resource allocation, stakeholder collaboration, and bureaucratic coordination in enhancing policy effectiveness. Proposed strategies include strengthening partnerships among government agencies, schools, NGOs, and parents, adapting curricula to local needs, empowering teachers, integrating digital tools for school zoning, and establishing independent monitoring mechanisms. The study underscores the broader societal impact of school zoning policies, advocating for equitable educational access as a driver for social cohesion and economic development. The academic implication combines education policy, public administration, and technological innovations, making it valuable for diverse academic and professional audiences. The practical implication of this study is that it provides a solution-driven approach, focusing on school zoning as a policy mechanism to promote equal educational opportunities. This appeals to policymakers and education stakeholders seeking practical strategies. Despite this, the findings offer useful insights. Future research should use mixed methods such as surveys and interviews to explore views from students, parents, teachers, and policymakers.